Estradiol Decline Before hCG Administration in COH Has a Negative Effect on IVF Outcomes in Patients Without OC Pretreatment - Zhu Y; Zheng Z; Fan B; Sun Y; Zhai J; Du Y (Dove Medical Press, 2024)
Yinci Zhu,1,2 Zhong Zheng,1,2 Bihong Fan,1,2 Yun Sun,1,2 Junyu Zhai,1,2 Yanzhi Du1,2 1Department of Reproductive Medicine, Ren Ji Hospital, Shanghai Jiao Tong University, School of Medicine, Shanghai, 200135, People's Republic of China; 2Shanghai Key Laboratory for Assisted Reproduction and Reproductive Genetics, Shanghai, 200135, People's Republic of ChinaCorrespondence: Junyu Zhai; Yanzhi Du, Department of Reproductive Medicine, Ren Ji Hospital, Shanghai Jiao Tong University, School of Medicine, Shanghai, 200135, People's Republic of China, Tel +86-21-20284525; +86-21-20284518, Email zhaijy2007@foxmail.com; duyz@sjtu.edu.cnPurpose: Together with ultrasound measurement of follicle size, serum estradiol (E2) provides guidance for controlled ovarian hyperstimulation (COH). However, during the COH process, some patients experience decreased serum E2 level, especially before human chorionic gonadotropin (hCG) trigger. In order to elucidate the effect of E2 reduction as well as the role of oral contraceptive pretreatment, a retrospective study was performed in our center from 2013 to 2019.Patients and Methods: In total, 333 patients who experienced an E2 decrease prior to hCG administration were recruited as E2 decline group, while 333 patients with continuously E2 increase during COH were considered as control group. Based on pretreatment strategy, the two groups were further categorized into oral contraceptive (OC) and non-OC sub-groups, and IVF and clinical outcomes were compared between paired groups.Results: Number of dominant follicles on hCG day and normally fertilized zygotes were significantly decreased in E2 decline group, and the significantly reduced live birth rate in E2 decline group indicated the close relationship between E2 decline and clinical outcomes. To analyse further, we found that in patients without OC pretreatment, the pregnancy rate and live birth rate of E2 decline group (n = 141) were significantly lower than control group (n = 136) (56.3% versus 68.0%, 50.8% versus 63.5%, respectively). However, for patients with OC pretreatment, no difference was detected between two groups, suggesting a potential effect of OC pretreatment on clinical outcomes.Conclusion: E2 decline prior to hCG-triggering day adversely affects IVF and clinical outcomes in patients without OC pretreatment, especially fertilization rate and live birth rate.Keywords: estradiol decline, controlled ovarian hyperstimulation, oral contraceptive, in vitro fertilization, fertilization rate, live birth rate